Laser and light-based treatments of venous lakes: a literature review. Issue 7 (September 2016) - Mlacker, Stephanie; Shah, Vidhi; Aldahan, Adam; McNamara, Colin; Kamath, Preetha; Nouri, Keyvan
Abstract Venous lake is a benign vascular malformation commonly seen in elderly patients, typically arising in sun-exposed areas of the body. Patients often seek treatment to prevent recurrent bleeding or because they find the lesion cosmetically unacceptable. Venous lake may negatively affect quality of life, due to the cosmetic disfigurement it can create and the resulting psychological distress. Traditional treatments, such as surgical excision, cryosurgery, sclerotherapy, and electrocoagulation, result in varying degrees of success and can cause discomfort. Laser- and light-based treatment modalities may offer a safe and effective alternative, as numerous studies have shown their benefit in the treatment of venous lakes, particularly with the long-pulsed 1064-nm neodymium-doped yttrium aluminum garnet (Nd:YAG). Although various types of lasers and lights have been studied, there remains a lack of general consensus as to which one is the superior laser modality. Further studies that establish standardized protocols to compare the results of using different types of laser treatments are warranted.